Scalable information system using event oriented programming and NoSQL - Santana, Vagner Jose [UNESP]; Souza, Gabriel Spadon de [UNESP]; Messias Correia, Ronaldo Celso [UNESP]; Garcia, Rogerio Eduardo [UNESP]; Eler, Danilo Medeiros [UNESP]; Olivete Junior, Celso [UNESP]; Rocha, A.; Dias, G. P.; Martins, A.; Reis, L. P.; Cota, M. P. (Ieee, 2015)
One of many challenges in a web information systems is the capability of staying stable and available as the number of users and requests increase rapidly, what we call scalability. This paper provides a model based on development of events-oriented applications, non-blocking in the environment Node. JS with the non-relational database model (MongoDB), preparing to establish scalability and a comparison with a traditional model (relational database (MySQL), HTTP Apache server and PHP language). The results obtained reveal that the proposed model is more efficient (response time of six to eight faster) than the comparative model, can be used in production environments with development quality, performance improvement and scalability.
Keywords: component: Node. JS; MongoDB; Scalability